Ways to develop logical thinking of primary school students - Sofiboeva Gulchekhra Mamurdjonovna; Tukhtasinov Mirzaolim Odiljon ugli (Peerian Journals Publishing, 2024)
This article discusses the effective methods of developing logical thinking skills of elementary school students, forming their geometric imagination.
Keywords: Thought; logic; logical thought; comparison